Developing Future Clinician Scientists while Supporting a Research Infrastructure. Issue 2 (18th April 2013) - Holsti, Maija; Adelgais, Kathleen M.; Willis, Leah; Jacobsen, Kammy; Clark, Edward B.; Byington, Carrie L.
Abstract Background Supporting clinical research is a national priority. Clinician scientists are rare and clinical trials in academic medical centers (AMC) often fail to meet enrollment goals. Undergraduate students interested in biomedical careers often lack opportunities to perform clinical research. Objective Describe an innovative undergraduate course that supports clinical research in an AMC. Methods The course, Clinical Research Methods and Practice, offers undergraduate students the opportunity to learn clinical research through didactic and practical experiences. The students in turn support clinician scientists' conduct of clinical studies in an AMC. Clinician scientists receive research support and participate in mentoring sessions for students. Results Over seven semesters, 128 students have assisted in 21 clinical studies located in outpatient and inpatient units of two hospitals. Students identified and screened eligible patients, collected clinical data, assisted in obtaining informed consent, and transported specimens. Many of the clinician scientists have met their enrollment goals and several have been top‐enrollers in multicenter clinical trials as a result of student support. Conclusions The Clinical Research Methods and Practice class addresses barriers to clinical research in AMC. This may be a model for institutions committed to mentoring students early in their career and to developing infrastructures for clinical research. Clin Trans Sci 2013; Volume 6: 94–97